2015
DOI: 10.14393/bj-v31n6a2015-30213
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, environmental effects and storage period in onion seeds quality

Abstract: ABSTRACT:In several species, seed longevity may be influenced by genotype and storage environment. It is scarce researches that evaluated those effects in onion seeds. From the exposed, it was aimed to evaluate the behavior from onion seeds of different genotypes stored in three conditions of relative humidity (25; 35 and 45% RH) monitored during six different storage periods. The research was executed at the Laboratório de Análise de Sementes e Recursos Genéticos from Universidade Federal de Uberlândia, Monte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
0
3
Order By: Relevance
“…In previous investigations [43], the germination rate ranged between 80 and 90%. According to Maciel and coworkers [44], the genotype plays an important role on seed germinability in interaction with temperature, which is deemed crucial even by other authors [45]. Mollah et al [21] reported that the 15 November planting time resulted in the highest seed germination rate (84%), whereas 1 and 16 October had the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…In previous investigations [43], the germination rate ranged between 80 and 90%. According to Maciel and coworkers [44], the genotype plays an important role on seed germinability in interaction with temperature, which is deemed crucial even by other authors [45]. Mollah et al [21] reported that the 15 November planting time resulted in the highest seed germination rate (84%), whereas 1 and 16 October had the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…Quanto maior a magnitude desses fatores, mais rapidamente as sementes se deterioram, ou seja, a germinação e o vigor reduzem progressivamente quando as sementes são expostas a condições inadequadas de armazenamento (Segnou et al, 2012). Assim, as condições de armazenamento e o teor de água das sementes, juntamente com a embalagem, têm um impacto direto na duração das sementes de várias hortaliças (Maciel et al, 2015).…”
Section: Armazenamento De Sementes De Pimentaunclassified
“…As espécies do gênero Capsicum são cultivadas principalmente pela agricultura familiar e são importantes representantes da agrobiodiversidade de um país (Carvalho et al, 2015). O gênero possui inúmeras aplicações comerciais, principalmente na indústria de cosméticos, farmacêutica, culinária e decoração (Ferraz et al, 2016).…”
Section: Introductionunclassified
“…Laime et al (2010) alcançaram de 72 a 100% de emergência de Inga ingoides dependendo da profundidade, as quais foram postas para secarem por um período de 12 horas, em ambiente de laboratório com temperatura de 24,5 ºC ± 0,5 °C. Desse modo, a emergência das plântulas é influenciada pelas práticas de semeadura, como a profundidade (FINCH-SAVAGE; BASSEL, 2016), bem como pelas condições de temperatura, e teor de umidade do ambiente de armazenamento, pois esta relação pode influenciar no equilíbrio de eventos metabólicos, no processo de deterioração e reações bioquímicas nas sementes, o que leva a perda do vigor (MACIEL et al, 2015;DIAS et al, 2016;NAGEL et al, 2016). A temperatura mais baixa pode ter causado danos relacionados a formação de cristais e ruptura das células consoante observações de Fonseca e Freire (2003), e a temperatura mais elevada pode ter provocado a degradação das membranas, fazendo com que no início da germinação a energia produzida fosse direcionada para recuperação destas membranas para assim dar início a germinação.…”
Section: Condições Do Armazenamentounclassified